Windows NT server 4 professional reference - Siyan, Karanjit (New Riders Pub., 1996)
"This is the only single-source reference that provides the information necessary to maintain Windows NT Server 4 in a diverse computing environment. You'll quickly master advanced installation and configuration procedures and be able to design and build efficient domain-based Windows NT networks; integrate Windows NT into existing Novell Networks; understand Windows NT browsing functions over Wide Area Networks; optimize Windows NT Server 4 performance; configure TCP/IP for Windows NT services; and implement Windows NT security and audit policies." "Organized for quick and easy reference, each chapter stands alone as a complete guide to a specific Windows NT Server 4 technology - such as security, supporting clients, printing, TCP/IP configuration, and application servers."--BOOK JACKET.